2014
DOI: 10.1080/08838151.2014.966365
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is Believing: Effects of Uncivil Online Debate on Political Polarization and Expectations of Deliberation

Abstract: The present study examines how exposure to uncivil online comments influences individuals' attitude polarization along political party lines, perceived political polarization of the public, and expectations about public deliberation. Findings show that exposure to uncivil online discussion does not affect attitude polarization, but it does significantly affect the perceived polarization of the public. In addition, exposure to uncivil online discussion leads to lower expectations about public deliberation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 30 publications
(27 reference statements)
1
75
1
4
Order By: Relevance
“…These results help to explain why incivility is prevalent in comment sections, even though journalists and news users decry uncivil content. Given that incivility is connected to polarization (Anderson et al, 2014;Hwang et al, 2014), this finding could be read as disconcerting. Combining theories about news values, social identity, and cognitive biases with a unique dataset from The New York Times revealed that there are incentives for incivility to exist in comments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results help to explain why incivility is prevalent in comment sections, even though journalists and news users decry uncivil content. Given that incivility is connected to polarization (Anderson et al, 2014;Hwang et al, 2014), this finding could be read as disconcerting. Combining theories about news values, social identity, and cognitive biases with a unique dataset from The New York Times revealed that there are incentives for incivility to exist in comments.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than promoting respectful discussions, comment sections can foster incivility toward other commenters and points‐of‐view (Coe, Kenski, & Rains, ). Incivility in news comment sections can lead to troubling consequences, such as prompting polarized attitudes about science (Anderson, Brossard, Scheufele, Xenos, & Ladwig, ) and toward political parties (Hwang, Kim, & Huh, ). It is also related to avoiding comment sections and online discussion (Diakopoulos & Naaman, ; Springer, Engelmann, & Pfaffinger, ) and perceiving articles as lower‐quality (Prochazka, Weber, & Schweiger, in press).…”
Section: Professional Norms and Journalists' Reactions To Uncivil Commentioning
confidence: 99%
“…However, when a major political event, such as a war, occurs and everybody is talking politics, political tolerance disappears and weak ties are broken, thus reducing the chances of political deliberation. Furthermore, as debates become ever more heated and uncivil, people's expectations of public deliberation would appear to decline (Hwang, Kim, & Huh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Polarized content in comment sections may also amplify further polarized comments (Muddiman & Stroud, 2017). What is more, online political dialogue has a tendency to increase political polarization and extreme viewpoints (Hwang, Kim, & Huh, 2014). However, research has yet to examine the extent to which comments "one-up" prior comments.…”
Section: Supplemental Analysismentioning
confidence: 99%